Sodium–aluminum–iron phosphate glasses as legacy high level waste forms. (January 2017) - Stefanovsky, S.V.; Stefanovsky, O.I.; Remizov, M.B.; Kozlov, P.V.; Belanova, E.A.; Makarovsky, R.A.; Myasoedov, B.F.
Abstract: Legacy liquid high level wastes (HLW) generated at former defense programs, which are under storage in stainless steel tanks at PA Mayak have high Fe/Al contents. They will be vitrified in a new EP-500 J-heated ceramic melter, which is planned to be commissioned in 2016. Like previous melters of the same type, the new melter will produce aluminophosphate based glass. Due to high content of iron oxides in the HLW the glass obtained will have base sodium–aluminum–iron phosphate composition. Complex sodium–aluminum–iron phosphate glassy materials with various Al2 O3 to Fe2 O3 ratio containing high level waste (HLW) surrogate were designed, produced, and characterized by X-ray diffraction and scanning electron microscopy. The samples were annealed by a canister centerline cooling regime at the EP-500 plant. Addition of B2 O3 and partial Fe2 O3 substitution for Al2 O3 in the materials increases resistance to devitrification whereas further substitution and NiO incorporation increase significantly tendency to devitrification. All the glasses had low leachability satisfying to Russian standard R 52126-2003 (similar to MCC-1 at 25 °C) but the glasses at Al2 O3 :Fe2 O3 ratio close to 1 were found to be the highest chemically durable. Highlights: Sodium aluminophosphate based glasses at low Fe2 O3  + NiO + Cr2 O3 content cooled at the regime simulating melt cooling in a canister filled with glass were found to be mostly X-ray amorphous and hydrolytically durable that makes them suitable as HLW forms. Introduction of ∼6 wt.% B2 O3 stabilizes vitreous state. Fe2 O3  + NiO substitution for Al2 O3 in amount of 7–8 wt.% favors devitrification and reduces hydrolytic durability of glasses. Particularly negative effect offers occurrence of sulfate ions.